Membangun Peran Inovasi UMKM, Literasi Finansial, Dan Pengembangan Kreativitas Anak Dalam Pemberdayaan Ekonomi Masyarakat Desa - Syarif Riezieq; Wenny Pebrianti; Iwan Setiawan; Tiara Nur Salsabila; Alfiyyah Zalfa Salsabillah; Augusta Genta Buwana (Pusat Riset dan Inovasi Nasional, 2025)
Kuala Secapah Village, located in Mempawah Hilir District, Mempawah Regency, West Kalimantan, has untapped MSME potential due to low digital technology adoption, a lack of understanding of financial literacy, and limited resources to channel children's creativity. The Tanjungpura University KKM-PKM program aims to increase community capacity through empowering local MSMEs, inclusive financial literacy, and developing children's creativity. Activities include training on marketplaces and MSME branding (such as Facebook Business, Shopee, and Instagram), financial literacy education using the Spreadsheet application, as well as key chain and bracelet craft workshops for children. Using a participatory approach, this program seeks to improve MSME competitiveness, community financial management skills, and the creativity of the younger generation. The program's results indicate an increase in participants' understanding of digital marketing and financial literacy, which supports local economic independence.